AB0757 Quality of life in Patients with Active Nonradiographic Axial Spondyloarthritis After 16 Weeks of Golimumab Treatment. (9th June 2015) - Maksymowych, W.P.; Curtis, S.; Dougados, M.; Bergman, G.; Huyck, S.; Tzontcheva, A.; Sieper, J.
Abstract : Background: Chronic inflammation, back pain, and progressive spinal stiffness associated with axial spondyloarthritis (axSpA) can decrease quality of life (QoL). Objectives: To determine whether golimumab (GLM) is superior to placebo (PBO) in improving the QoL of patients with nr-axSpA. Methods: GO-AHEAD was a double-blind, randomized, PBO-controlled trial of GLM in patients with active nr-axSpA (ASAS criteria and centrally read sacroiliac joint X-rays and MRI, disease duration ≤5 years, chronic back pain, high disease activity [total back pain ≥40 mm on a 0–100 mm VAS and BASDAI ≥4 cm], and inadequate response/intolerance to NSAIDs). Patients were randomized 1:1 to SC GLM 50 mg or PBO every 4 wk. Secondary outcomes related to QoL included the 36-item Short Form Health Survey (SF-36), Ankylosing Spondylitis Quality of Life (ASQoL), EuroQoL 5-Dimension (EQ-5D) Index and Health State (0–10 cm VAS), and Work Productivity and Activity Impairment (WPAI) questionnaire scores at wk 16. Treatment group differences for all patients and for the objective signs of inflammation (OSI) population (baseline inflammation by centrally evaluated SI MRI and/or elevated CRP) were compared using a constrained longitudinal data analysis for continuous endpoints and Mann–Whitney test for WPAI scores. Results: Of 197 treated patients (GLM=97, PBO=100), mean age was 31 years; 57% were male. At wk 16, patients treated with GLM had greater improvements from baseline QoL than patients treated with PBO, as measured by all scales of the ASQoL, EQ-5D, and SF-36 (table ). GLM patients also had greater improvements than PBO patients in percentages of WPAI overall work impairment (−21.1 vs −11.7, P =0.0391) and activity impairment (−24.9 vs −8.6, P <0.0001); impairment while working and work time missed were not significantly different between groups. Results for QoL and WPAI measures were similar in the OSI population, except that patients in the GLM group also had greater improvements in percentage of impairment while working than the PBO group ( P =0.0194). Conclusions: Patients with active nr-axSpA who received GLM treatment had greater improvement in QoL and work productivity outcomes at wk 16 than those who received PBO, although the mean values indicate that some degree of impairment remained. Disclosure of Interest: W. Maksymowych Grant/research support from: AbbVie, Janssen, Pfizer, Consultant for: AbbVie, UCB, Pfizer, Merck, Janssen, Eli Lilly, Celgene, Synarc, S. Curtis Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, M. Dougados Grant/research support from: AbbVie, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, G. Bergman Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, S. Huyck Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, A. Tzontcheva Employee of: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, J. Sieper Consultant for: AbbVie, Eli Lilly, Janssen Biologics, Merck, Novartis, Pfizer, Roche, UCB